2004
DOI: 10.1097/01.hp.0000133216.72557.ab
|View full text |Cite
|
Sign up to set email alerts
|

Latency and the Lung Cancer Epidemic Among United States Uranium Miners

Abstract: The latency of occupational cancer was a key factor in the recent epidemic of lung cancer among U.S. uranium miners. A review of the epidemic and analysis of latency periods with a near lifetime follow-up found that among former and nonsmokers, the mean mid-induction latent period is nearly a constant at about 25 y, regardless of age at starting or magnitude of exposure. Among cigarette smokers, the mean is shorter (about 19 y). It is not influenced by age at start of smoking, amount smoked, or magnitude of ex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
26
0

Year Published

2006
2006
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 40 publications
(28 citation statements)
references
References 11 publications
2
26
0
Order By: Relevance
“…For the Colorado miners, the highest risk was estimated for 14 years since exposure (Hauptmann et al, 2001) and 17 years since exposure (Kreisheimer, 2006), based on different statistical approaches. When taking into account the American Underground Uranium Miners (UGUM) data set, the radon-related mean latency period was estimated as 25 years for former and nonsmokers and 19 years for cigarette smokers, respectively (Archer et al, 2004). Figure 1 Lung cancer risk in relation to exposure rate, given in WL, for different groups of accumulated exposure (italic figures give upper limit of 95% CI).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…For the Colorado miners, the highest risk was estimated for 14 years since exposure (Hauptmann et al, 2001) and 17 years since exposure (Kreisheimer, 2006), based on different statistical approaches. When taking into account the American Underground Uranium Miners (UGUM) data set, the radon-related mean latency period was estimated as 25 years for former and nonsmokers and 19 years for cigarette smokers, respectively (Archer et al, 2004). Figure 1 Lung cancer risk in relation to exposure rate, given in WL, for different groups of accumulated exposure (italic figures give upper limit of 95% CI).…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, ERR/WLM was modified by either duration of exposure or concentration. Since that study, new analyses of the North American and the Chinese cohorts have been published Stram et al, 1999;Hauptmann et al, 2001;Hornung, 2001;Duport, 2002;Archer et al, 2004;Kreisheimer, 2006), yet further follow-up was only conducted for the Czech (Tomásek, 2002;Tomásek and Zarska, 2004) and the French cohort (Rogel et al, 2002;Laurier et al, 2004). Although the evidence of a radon-related lung cancer risk among miners is large, it is based upon various heterogeneous cohorts for which the cohort-specific risk estimates vary by more than an order of magnitude.…”
mentioning
confidence: 99%
“…Our study has long follow-up times, and, therefore, it was possible to test for long latency times, something that is especially important when lung cancer data are analyzed. Archer et al (29) found that the latency period for uranium miners was about 25 years for nonsmokers and 19 years for smokers. Norwegian studies by Romunstad and Rønneberg and their coworkers (8,13,18,27,28) are the only cohort studies on aluminum smelters that have tested for latency times as long as 30 years.…”
Section: Discussionmentioning
confidence: 99%
“…96 Of continuing controversy today is the lack of protective equipment and ventilation in American uranium mines following World War II. 97 In consideration of the health effects experienced by American uranium miners, the Radiation Exposure Compensation Act was passed by the US Congress in 1990, providing compensation to miners who developed health problems related to their radiation exposure. Despite being amended in 2000, controversy remains as to whether Radiation Exposure Compensation Act adequately covers all those with adverse health effects from working in uranium mines.…”
Section: Current Regulationsmentioning
confidence: 99%